ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2016 – 2018 - kadari, kadari (PRIMA EKONOMIKA, 2020)
The purpose of this study was to examine the partial and simultaneous influence of the factors of profitability, solvency, company size, size of KAP, and the audit committee on Audit Delay. The type of research used is assosiative explanatory research. The sample selected in this study takes the purposive sampling method that involved 64 companies during the period 2016-2018, as a result the number of data used is 192 observational data. Quantitative data are in the form of financial reports downloaded from the IDX website and the website of the company concerned. Data collection techniques using secondary data. The data analysis were descriptive statistics, classic assumption tests (normality test, multicollinearity test, autocorrelation, and heteroscedasticity test); and multiple linear regression analysis (t test, F test, and coefficient of determination). The t test conducted has shows that profitability and company size have a negative effect on audit delay, solvency has no effect on audit delay, and the size of KAP and audit committee has a positive effect on audit delay. The results of the F test simultaneously show that profitability, solvency, company size, KAP size, and audit committee have an effect on audit delay. The value of the coefficient of determination (Adjusted R Square) is 22.4% while the remaining 77.6% that influenced by other factors that are not examined. Keywords: Profitability, Solvency, Company Size, KAP Size, Audit Committee, Audit Delay